Clinical performance of resin composite restorations placed by dental students - Daiane Cristina Mendonça dos Santos; João Felipe Besegato; Joissi Ferrari Zaniboni; Solange de Paula Ramos; Sueli de Almeida Cardoso; Márcio Grama Hoeppner (Universidade Estadual de Campinas, 2022)
Aim: A retrospective, cross-sectional study was carried out to evaluate the performance of resin composite restorations placed by undergraduate dental students with 1 to 15 years of placement based on dental records. Methods: Four calibrated operators evaluated 498 restorations (anterior and posterior) of 120 patients according to Ryge's validated criteria (USPHS). Results: The criteria that showed the smallest changes between the types of failures were color matching, marginal discoloration and surface texture. Regarding the longevity, the surface texture showed an increase in the frequency of failures from the second time interval (3.1 to 6 years). Higher prevalence of failure was found in class II and III restorations, with secondary caries being the main reason. No significant differences were found for anatomic form, marginal adaptation, and color matching. Class V restorations showed a higher fracture rate with total displacement of the restoration, with no increase in the frequency of fracture over time. Conclusion: High rate of restoration failure was observed, possibly due to the lack of experience and skills of the students. This outcome highlight the need for continuous revision and improvements of teaching practice regarding the development of clinical competences and skills by dental students.